Implications of the Enactment of Law Number 1 of 2023 concerning the Criminal Code on Potential Conflicts of Norms and the Effectiveness of Enforcement of Corruption Crimes in Indonesia - Gerald Elisa Munthe (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP) represents a major reform in Indonesia's criminal law system. However, its implementation raises critical concerns regarding potential normative conflicts with the Anti-Corruption Law (Law Number 31 of 1999 as amended by Law Number 20 of 2001), which has long served as a lex specialis in combating corruption as an extraordinary crime. This study aims to analyze the normative conflicts between the new Criminal Code and the Anti-Corruption Law, as well as their implications for the effectiveness of corruption law enforcement in Indonesia. Using a normative legal method with statutory and conceptual approaches, the research finds that potential inconsistencies exist in the formulation of criminal acts, criminal liability (especially corporate liability), sentencing systems (including minimum penalties and asset forfeiture), and the application of legal principles such as lex specialis derogat legi generali. These inconsistencies may lead to legal uncertainty, create opportunities for offenders to exploit legal loopholes through forum shopping, and result in disparity in court decisions. Furthermore, the dualism between the general criminal code and the special anti-corruption law weakens the deterrent effect of punishment and reduces public trust in the criminal justice system. From the perspective of legal effectiveness theory, the lack of harmonization undermines the system's ability to achieve justice and legal certainty. Therefore, regulatory harmonization and a clear affirmation of the hierarchical relationship between these legal norms are necessary to ensure consistency within the legal system and to strengthen the effectiveness of anti-corruption enforcement in Indonesia.